Metabolic regulation of pathways of carbohydrate oxidation in potato (Solanum tuberosum) tubers - Centeno, Danilo C; Oliver, Sandra N; Nunes-Nesi, Adriano; Geigenberger, Peter; Machado, Daniel N; Loureiro, Marcelo Ehlers; Silva, Marco A.P; Fernie, Alisdair R (Physiologia plantarum, 2008)
In the present article we evaluate the consequence of tuber-specific expression of yeast invertase, on the pathways of carbohydrate oxidation, in potato (Solanum tuberosum L. cv. Desiree). We analysed the relative rates of glycolysis and the oxidative pentose phosphate pathway that these lines exhibited as well as the relative contributions of the cytochrome and alternative pathways of mitochondrial respiration. Enzymatic and protein abundance analysis revealed concerted upregulation of the glycolytic pathway and of specific enzymes of the tricarboxylic acid cycle and the alternative oxidase but invariant levels of enzymes of the oxidative pentose phosphate pathway and proteins of the cytochrome pathway. When taken together these experiments suggest that the overexpression of a cytosolic invertase (EC 3.2.1.26) results in a general upregulation of carbohydrate oxidation with increased flux through both the glycolytic and oxidative pentose phosphate pathways as well as the cytochrome and alternative pathways of oxidative phosphorylation. Moreover these data suggest that the upregulation of respiration is a consequence of enhanced efficient mitochondrial metabolism.